The effect of entrepreneurial orientation dimensions on takaful agency’s business performance in Malaysia - Muhamad Azrin Nazri,; Kalsom Abd. Wahab,; Nor Asiah Omar, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study aimed to examine the relationship among the five dimensions of entrepreneurial orientations (innovativeness, risk taking, autonomy, competitive aggressiveness, and proactiveness) and performance of Takaful agencies in Malaysia. A total of 211 questionnaires were collected via purposive sampling from Takaful agency’s managers from three main Takaful operators namely Etiqa, Takaful Malaysia and Takaful Ikhlas. A structural equation model that assessed the relationship between the proposed variables was tested using PLS 2.0. The findings revealed that of the five dimensions of entrepreneurial orientation, proactiveness and autonomy were found to have significant influence on business performance